PERAN KOMISI I DPR RI DALAM MEMBANTU PENYELESAIAN KASUS PEKERJA MIGRAN INDONESIA (PMI) DI LUAR NEGERI - M Nurkholis; Ermas Ratu Malika; Adam Nugraha; Saepul Umar (Jurnal Riset Multidisiplin Edukasi, 2025)
Protection of Indonesian Migrant Workers (PMI) abroad is a constitutional obligation of the state, stemming from the 1945 Constitution of the Republic of Indonesia and further elaborated in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. In its implementation, the protection of PMI involves various state institutions, both executive and legislative. The House of Representatives of the Republic of Indonesia (DPR RI), through Commission I, which oversees foreign relations and diplomacy, plays a strategic role in carrying out its oversight function, parliamentary diplomacy, and policy facilitation in resolving PMI cases abroad. However, the high number of problematic PMI cases, particularly in destination countries such as the Middle East, indicates a persistent gap between legal norms and protection practices in the field. This study aims to analyze the role of Commission I of the DPR RI in assisting in resolving PMI cases abroad and to assess the effectiveness of existing legal regulations in supporting this role. This research uses a normative legal research method with a statute approach and a conceptual approach. The legal materials analyzed include the 1945 Constitution of the Republic of Indonesia, Law Number 17 of 2014 concerning the People's Consultative Assembly (MPR), the House of Representatives (DPR), the Regional Representatives Council (DPD), and the Regional People's Representative Council (DPRD), Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, and relevant legal regulations and doctrines. The research results indicate that, normatively, existing legal arrangements provide sufficient authority for Commission I of the Indonesian House of Representatives (DPR RI) to carry out its role as a supervisor and facilitator in resolving cases involving Indonesian migrant workers abroad. This role is realized through political oversight mechanisms, parliamentary diplomacy, and the provision of policy recommendations to the government and relevant ministries. However, the effectiveness of these legal arrangements in practice remains suboptimal due to the non-binding nature of DPR recommendations, weak inter-institutional coordination, and the DPR's limited authority in the technical and operational spheres. Therefore, strengthening the regulatory framework and institutional mechanisms is necessary to ensure that Commission I's role is not only normative and legitimate but also has a more effective driving force in ensuring the ongoing legal protection of Indonesian migrant workers abroad.